Munculnya Penenun Laki-Laki Di Industri Tenun Songket Pandai Sikek, Tanah Datar (1998-2022) - Eko Ilham Saputra; Siti Fatimah (Jurusan Sejarah FIS UNP, 2023)
ABSTRACT Songket is a beautiful and luxurious fabric with a weave made of sparkling-looking gold or silver thread. Technically, songkets are woven on a loom called a panta with a braid of wire and gold-patterned threads on its transverse winding. In other words, Songket is a form of expression of beauty that combines creativity and intelligence. Songane weaving skills are not something that can be obtained, but rather must be learned, because meticulousness and patience are required in the process of weaving. Minangkabau songket cloth has actually existed for more than a hundred years. During this time, songket weaving